MUSIC AND DANCE AS MEDICINE: AN ART BEYOND EMOTIONAL EXPRESSION FOR HEALING - Jebuni, T. S.; Jebuni, F. Y. T.; Adum-Atta, K. (UDS International Journal of Development, 2020)
The paper examines current developments on the use of music as therapy. It looks at the application of musical healing by the society in contemporary times and determines extent to which it affects the emotions of people. The objectives of the paper were to review literature from anthropologists, ethnomusicologists and historians on using dance and music as a scientific approach to healing the sick. Through interview, participant observation and content analysis, the paper examines the JinÅ‹wariba (dancing prophet) musical therapeutic of the Dagbamba of Northern Ghana, and discusses the specific purposes of the Jinwaraba shrine music and dance healing. Results of the findings were choreographed for stage performances for public education. Keywords: Emotions, Healing, Therapy, Jinwariba